A Modified Double Staggered Grating Waveguide Slow Wave Structure for Sub-THz Traveling Wave Tubes - Zhao, Chen; Xu, Hang (IEEE transactions on electron devices, 2023)
A modified double staggered grating waveguide (DSGW) slow wave structure (SWS) is proposed for millimeter-wave and sub-THz traveling wave tubes (TWTs). Gratings with a cross section outline of exponential curves are applied instead of the traditional rectangular cross section. The proposed SWS owns a higher interaction impedance compared to DSGW, resulting in higher output power and gain. With proper design and optimization of the input-output couplers, the proposed SWS can have a wide - 15 dB impedance bandwidth, extending from 192 to 230 GHz. Particle-in-cell (PIC) simulations are carried out for a TWT with sheet electron beam (SEB) and the main SWS having 70 periods. Such a TWT provides a maximum power of 116.64 W which indicates a significant improvement compared with the traditional DSGW.